PENYULUHAN DAMPAK DAN BAHAYA JUDI ONLINE SERTA SOSIALISASI FATWA MPU ACEH NOMOR 01 TAHUN 2016 TENTANG JUDI ONLINE PADA REMAJA GAMPONG UJONG BAROH MEULABOH - Tio Devilishanti; Jusnaini Hasni; Abu Hassan Makmun; Desi Yuliana; Mutiara Shifa (Gapenas Publisher, 2024)
The rise of online gambling in society is increasingly concerning. The Financial Transaction Reports and Analysis Center (PPATK) found that financial transactions related to online gambling reached IDR 101 trillion until the first quarter of 2024. Raids carried out by the authorities often catch online gambling perpetrators not only adults but also teenagers. The method used in this community service activity is to conduct presentations in delivering materials and interactive discussions with participants. The activity results show that most teenagers gamble online because they start with curiosity and want to know. Hence, they decide to try it first until they finally become addicted. This community service activity is one of the activities that support the Aceh Government's efforts to eradicate gambling activities, especially in the West Aceh Region. The results of this activity are expected to provide awareness and early prevention for teenagers so that they do not fall too far into activities that are not beneficial and have many negative effects that will ultimately hinder the productivity of teenagers